INVESTIGATING THE EXPERIENCES OF STUDENTS WITH DISABILITIES WITH E-LEARNING DURING THE COVID-19 PANDEMIC IN VIETNAMESE HIGHER EDUCATION - Hoang Thien Nguyen; Thi Ngoc Nga Nguyen; Thi Kim Cuc Ly; Dong Khanh Nguyen; Hoang Thao Nhi Ho; Thi Hong Nhung Truong (Tạp chí Khoa học Đại học Đà Lạt)
This study uses a mixed-methods approach to investigate the experiences of Vietnamese university students with disabilities (visual/mobility impairments) with e-learning as a consequence of emergency remote teaching during the COVID-19 pandemic. An analysis of the ideas of 20 surveyed students with disabilities at eight universities in Ho Chi Minh City and six students interviewed afterward shows that students can change their study habits to adapt to e-learning and to enjoy this model of learning. However, the participants revealed that they also want to experience face-to-face learning so that they can interact with their lecturers and peers more effectively and in more diverse ways, as well as assimilate lectures more easily. Furthermore, the research shows that various adjustments should be made by system designers, universities, and lecturers to make e-learning friendlier to disabled students. The recommended adjustments include designing easy-to-use learning tools and platforms, providing lecturers with the necessary tools and facilities to design lessons appropriate for all students, providing psychological and technical support for disabled students, choosing user-friendly learning applications and platforms, providing students with suitable learning resources, and modifying testing and assessment methods.